Mulheres homicidas: contribuições da psicologia e do direito - Melo, Fabiana Passos de (2018)
The objective of this dissertation is to describe characteristics of the behavior of homicidal female through three scientific papers. The first proposes research on the states of Brazilian women from the model of societies of the old regime, with considerations about the tradition in the colonial period and references to legislative ruptures in the nineteenth and twentieth centuries, such as the acquisition of full capacity, equality in rights and obligations in the family, divorce, the stable union and the one-parent family, as well as the decriminalization of conduct that is detrimental to customs. In the end, there are coincidences with the female behavior described by psychology. Then a systematic review of literature aims to describe the typology of homicide practiced by women. When the PRISMA protocol was applied, the corpus of analysis consisted of 15 articles located in international databases, whose variables were synthesized in: homicide profile, its relationship with the victim and crime scene, modus operandi and motivation. It was observed that 63.2% of the offenders were unemployed, that 71.66% lived in unfavorable economic conditions and had low schooling (only 7.23% finished higher education). There are coincidences with the female behavior described by psychology. The second article is a systematic review of literature that aims to describe the typology of homicide practiced by women. By PRISMA protocol, the corpus consisted of 15 articles located in international databases, whose variables were synthesized in: homicide profile, its relationship with the victim and crime scene, modus operandi and motivation. It was observed that 63.2% of the offenders were unemployed, that 71.66% lived in unfavorable economic conditions and had low schooling (only 7.23% finished higher education). It was evidenced that 90.05% of the victims were intimate partner, another relative or familiar person, and in 70.68% of the cases the crime was related to the history of this relationship. It was noticed that in 90.05% of the crimes, guns were used in the domestic environment, a circumstance linked to the crime scene, which, in 69.44% of the crimes, was the homicide / victim's residence. There was a history of violence or neglect of 64.4% of aggressors, mention of psychological or mental disorder by 83.9% of them and use of narcotic substances or alcohol by 48.15% of women. The third article aims to describe the typology of homicidal women from judicial proceedings of the 1st and 2nd Plenary Courts of the Jury Court of the Central Forum of the Region of Curitiba, through access to the Digital Judicial Process of the Judiciary of the State of Paraná (PROJUDI). Six cases were selected from 01/01/2012 to 12/31/2016, by the female gender in the "accused" field, whose data were collected in individual files, considering three categories of variables: homicide profile, profile of the victim, and description of the crime regarding location and modus operandi. They stood out: low educational level, unfavorable income and professional occupation of little qualification. It was observed the motivation related to family and professional conflicts, and that the victims are familiar, intimate partner or acquaintance, circumstances that influence the crime scene have always been residence of the victim or the aggressor, and the weapon of crime being of the domestic environment (knife, ax, bandage and poison). Highlights were: the precedents of violence in the past of the offender and the presence of mental problems.